Back Matter - JTSiskom Volume 5 Nomor 4 Tahun 2017 - JTSiskom, Ketua Editor (Jurnal Teknologi dan Sistem Komputer, 2017)
This article contains back-matter of JTSiskom Volume 5 Issue 4 Year 2017, which includes the author's index, author guidelines, copyright notice and its transfer agreement, publication ethics statements and journal content licenses.